Tin(II) n-butyl L-lactate as novel initiator for the ring-opening polymerization of ε-caprolactone: Kinetics and aggregation equilibrium analysis by non-isothermal DSC - Winita Punyodom (2018)
© 2017 Elsevier B.V. The catalytic behavior of the novel tin(II) n-butyl L-lactate (Sn(OCH(CH 3 )COOnC 4 H 9 ) 2 ) initiator in the ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) was firstly investigated by non-isothermal DSC. The Sn(OCH(CH 3 )COOnC 4 H 9 ) 2 initiator was successfully synthesized from the reaction of tin(II) chloride (SnCl 2 ), diethylamine (Et 2 NH) and n-butyl L-lactate (CH 3 CH(OH)COOnC 4 H 9 ). The synthesized Sn(OCH(CH 3 )COOnC 4 H 9 ) 2 was characterized by FT-IR, 1 H NMR and 13 C NMR techniques. The advantages of this initiator were high oxygen-moisture stability and solubility in common organic solvent. From DSC analysis, the polymerization rate of ε-CL was controlled by Sn(OCH(CH 3 )COOnC 4 H 9 ) 2 concentration. The average values of activation energy (E a ) obtained from Starink isoconversional method for the ROP of ε-CL initiated by 1.0, 2.0 and 3.0 mol% of Sn(OCH(CH 3 )COOnC 4 H 9 ) 2 were 74 ± 5, 72 ± 5 and 68 ± 2 kJ/mol, respectively. Furthermore, the aggregation and non-aggregation equilibrium of Sn(OCH(CH 3 )COOnC 4 H 9 ) 2 initiator in the ROP of ε-CL was also investigated by non-isothermal DSC. The degree of aggregation (m) of initiator was rapidly determined using new derived equation based on non-isothermal DSC approach. The polymerization mechanism was also studied and proposed through the coordination-insertion mechanism.